2017
DOI: 10.1016/j.rmcr.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Case report on pulmonary disease due to coinfection of Mycobacterium tuberculosis and Mycobacterium abscessus : Difficulty in diagnosis

Abstract: Mycobacterium abscessus, which is ubiquitous environmental organism, is more likely to cause pulmonary infection in the presence underlying lung disease and immunosuppression. We report a case of pulmonary disease due to coinfection of Mycobacterium tuberculosis (MTB) and Mycobacterium abscessus (M. abscessus) in an immunocompetent patient without underlying lung disease.Healthcare professionals should be aware of co-infection with MTB and M. abscessus, and treatment should be based on clinical suspicion and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
2
4
0
1
Order By: Relevance
“…20,21 Our study also showed co-infection with MTB and NTM in 14 women. Moreover, in nine of these women, NTM were positive both in the endometrium and in the POD aspirate.…”
Section: Main Findingssupporting
confidence: 63%
See 1 more Smart Citation
“…20,21 Our study also showed co-infection with MTB and NTM in 14 women. Moreover, in nine of these women, NTM were positive both in the endometrium and in the POD aspirate.…”
Section: Main Findingssupporting
confidence: 63%
“…There have been reports on concomitant infection with MTB and NTM in pulmonary disease. 20,21 Our study also showed co-infection with MTB and NTM in 14 women. In the study by Jain et al 22 one of the risk factors found to be associated with NTM infection was a past or present history of tuberculosis.…”
Section: Main Findingssupporting
confidence: 63%
“…Additionally, patients suffering from cystic fibrosis or other immunosuppressive condition can be infected by different mycobacteria at the same time. In fact, co-infections with M. abscessus and M. tuberculosis have been reported [27, 28]. The strong bactericidal effect of FP-11g against M. smegmatis supports investigation of this compound and its derivatives for its potential use as a broad antimycobacterial agent.…”
Section: Discussionmentioning
confidence: 95%
“…abscessus and M . tuberculosis have been reported [34, 35]. The strong bactericidal effect of FP-11g against M .…”
Section: Discussionmentioning
confidence: 99%